2014
DOI: 10.5901/ajis.2014.v3n3p393
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Development of Internal Marketing Orientation in the Private High Education Institutions in Albania

Abstract: In the post-communist era, Albanian higher education system underwent a series of reforms, which included the privatization of higher education institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Students with disabilities have a very low initial enrollment rate. In addition, they are more likely to drop out without graduating (Shima & George, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Students with disabilities have a very low initial enrollment rate. In addition, they are more likely to drop out without graduating (Shima & George, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When the focus is on external opportunities, institutional risk from partnerships is not always properly evaluated (Shima, George, 2014). New competencies need to be developed institutionally in order to take advantage of external opportunities and faculty embracing the change is crucial here.…”
Section: Resultsmentioning
confidence: 99%
“…Study of Siddiqi and Sahaf (2007) identified organizational communication, training and development, and employee motivation as key dimensions of internal marketing that need to be stressed upon to improve organizational performance. Furthermore, the researchers added that internal communication activities are important elements of internal marketing in the university context, which must be aimed at achieving employee satisfaction (Schuller andChalupsk, 2011, Shima andGeorge, 2014). Safi, Saleh, Begum, and Khan (2015) explored internal marketing through it four main dimensions: rewards, communication, employee training, and performance evaluation and found that it has a directly and positively improve the academic service quality.…”
Section: Role Of Internal Marketing In Determiningmentioning
confidence: 99%